Bahasa Inggris - Asrah Rezki Fauzani; Mutia Putri; Sechilia Vita; Wiandira, Cut Belva; Cut Hayyu Sartika; Mutiara Sani Lumban Gaol (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to develop a video tutorial on curling design based on active learning and to test its feasibility as a learning medium. This study uses the Research and Development (R&D) approach using the ADDIE model which consists of five main stages: analysis, design, development, implementation, and evaluation. The research subjects were 60 students from the Cosmetology Education Study Program, Faculty of Engineering, divided into small, medium, and large group trials. The data collection technique used a validation questionnaire from material experts, media experts, and student responses. The results showed that the validation from material experts obtained a percentage of 92% (very feasible) and from media experts 88% (very feasible). The small group trial obtained 89%, the medium group 90%, and the large group 91% with a very good category. Overall, the video tutorial media obtained a percentage of 90.29% with a very feasible category. Thus, video tutorials based on active learning are effective for improving students' understanding of the curling design course.